A Comprehensive Review On Cold Work Of AISI D2 Tool Steel - Salleh, Mohd Shukor; Minhat, Mohamad; Hussein, Nur Izan Syahriah; Abdul Rahim, Mohd Aidil Shah (EDP Sciences, 2018)
As a common material in mould and die application,AISI D2 cold work tool steel has proven to be a promising chosen material in the industries.However,challenges remain in using AISI D2 through a modified version with a considerable progress having been made in recent years. This paper provides a critical review of the original as-cast AISI D2 cold work tool steel up to the modified version.The main purpose is to develop an understanding of current modified tool steel trend;the machinability of AISI D2 (drilling,milling,turning,grinding and EDM/WEDM; and the microstructure evolution and mechanical properties of these cold work tool steels due to the presence of alloy materials in the steel matrix.The doping of rare earth alloy element,new steel fabrication processes,significant process parameter in machinability and surface treatment shows that there have been few empirical investigations into these cold work tool steel alloys.This study has discovered that cold work tool steel will remain to be explored in order to survive in the steel industries.